TEKNOLOGI FERMENTASI HIJAUAN LOKAL (SILASE) SEBAGAI SOLUSI PAKAN TERNAK BERKELANJUTAN UNTUK PETERNAK KAMBING SKALA RUMAH TANGGA - Agrienta Bellanov; Desrina Yusi Irawati (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
The scarcity of forage during the dry season is a major challenge for goat farmers in Senden Village, Kampak District, Trenggalek Regency. This condition negatively affects livestock productivity and the sustainability of smallholder farming. This community service program aimed to introduce silage technology as an appropriate solution for providing alternative feed that is nutritious, durable, and cost-effective. The implementation methods included socialization, technical training, production assistance, and evaluation of the impact on livestock health and productivity. Local forages such as elephant grass, corn leaves, and banana fronds were chopped, compacted, and fermented using EM4 and molasses. The results showed that the farmers were able to independently produce silage with an initial capacity of 300 kg per month. The program demonstrated tangible impacts, including increased goat weight within two months, reduced feed costs by up to 25%, and the establishment of the Fermented Feed Business Group (Kelompok Usaha Pakan Fermentasi/KUPF), which strengthened farmer solidarity. This program proves that a participatory approach based on simple technology can enhance food security and empower rural communities, and it offers a replicable model for other villages with similar conditions.